Design of a DLT-based document management system in road transport - Roger Heines; Sandro Rüttimann; Reinhard Jung (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: While the transportation sector enters a new phase of digital transformation, Distributed Ledger Technologies brought a new paradigm in the design of IS with numerous pilot-cases in logistics. Despite the various benefits (e.g., security, availability) little is empirically known about the development of such solutions. Where practitioners face numerous design decisions, we complement research by deriving six design principles for the construction of an applicable artifact in road transport. Methodology: We follow design-science-research to generate design knowledge based on a literature review, a morphological analysis, and case studies on DLT-driven applications for document management. We refine the results and demonstrate practicability via an instantiation based on expert interviews to provide generalizability in terms of actionable guidelines. Findings: We extend theory showing that DLT is an effective solution for cross-border information exchange. The design principles address the data architecture, access and storage across multiple stakeholders, and the way how data is exchanged. The results may further accelerate the adoption of DLT-based applications in logistics. Originality: We bridge the gap between technology and practical utilization by evaluating existing cross-industry use cases combining elements from the business, legal, and information technology perspective. Additionally, the instantiation of an applicable solution is further the result of an inter-organizational development process involving feedback of various practitioners (e.g., carrier, authorities).
urn:nbn:de:gbv:830-882.0161835; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Artificial Intelligence; Blockchain